Pidana Kerja Sosial Salah Satu Alternatif Mengurangi Kelebihan Kapasitas Di Lembaga Pemasyarakatan - Rudi Hartono Nainggolan (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
: Overcrowding in Indonesia’s prisons has become a pressing issue, with inmate numbers far exceeding the available space. This not only strains the correctional system but also affects the well-being of both inmates and prison staff. One possible solution is community service punishment, a concept rooted in utilitarianism, which prioritizes policies that benefit society as a whole. Instead of serving time behind bars, minor offenders would contribute to their communities through meaningful work, helping to ease the burden on the prison system. This study explores how social work punishment could be implemented in Indonesia to address overcrowding and examines the factors that could support its success. Through a legal and conceptual analysis, the findings suggest that this alternative approach not only reduces the prison population but also aids in the rehabilitation of offenders and contributes to social development. Looking at countries like the Netherlands and Portugal, where similar programs have been successful, we see evidence that community service punishment can lower repeat offenses and improve the overall efficiency of the correctional system. That said, Indonesia still faces challenges in making this a reality. Infrastructure remains limited, public opinion leans heavily toward imprisonment, and law enforcement agencies need to be well-prepared to oversee such a shift. For this policy to work, clear regulations, strong oversight, and cooperation between the government, society, and private sector are essential. With the right strategy, social work punishment could become a humane and sustainable solution to Indonesia’s overcrowded prisons, offering both offenders and society a better path forward.